1996
DOI: 10.1074/jbc.271.17.10169
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Increases Production of β-Amyloid Precursor Protein and β-Amyloid (Aβ) in Mammalian Lenses, and Aβ Has Toxic Effects on Lens Epithelial Cells

Abstract: Many amyloid diseases are characterized by protein aggregations linked to oxidative stress. Such diseases including those of the brain, muscle, and blood vessels exhibit plaques containing beta-amyloid (Abeta). Here we demonstrate that Alzheimer's precursor protein (betaAPP) and A beta are present at low levels in normal lenses and increase in intact cultured monkey lenses treated with H2O2 or UV radiation (known cataractogenic agents), and with phorbol 12-myristate 13-acetate. AP-1 factor binding, shown by ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(98 citation statements)
references
References 62 publications
5
92
1
Order By: Relevance
“…If Aβ is indeed aggregating in the AD lens, leading to these cataracts, it is possible that the initial molecular changes could be detected non-invasively as an early screening or diagnostic test. Further research is needed to establish the specificity of these cataracts and lens Aβ aggregations to AD, since both AβPP and Aβ have been shown to increase in concentration in the normal mammalian lens in response to UV radiation or other oxidative effects [109].…”
Section: (Figure 3)mentioning
confidence: 99%
“…If Aβ is indeed aggregating in the AD lens, leading to these cataracts, it is possible that the initial molecular changes could be detected non-invasively as an early screening or diagnostic test. Further research is needed to establish the specificity of these cataracts and lens Aβ aggregations to AD, since both AβPP and Aβ have been shown to increase in concentration in the normal mammalian lens in response to UV radiation or other oxidative effects [109].…”
Section: (Figure 3)mentioning
confidence: 99%
“…For example, Paola et al 25 and Frederikse et al 26 reported that intracellular Ab production increased as a result of oxidative stress in culture systems. In addition, Aplet et al 27 established the correlation between aging-related increases in oxidative stress and b-secretase activity with Ab plaque formation in a mouse model of AD.…”
Section: Discussionmentioning
confidence: 99%
“…The crystalline lens also could be involved in AD, and high levels of β-amyloid were described in lens epithelia of subjects with a particular and rare type of cataract, the anterior subcapsular cataract [73,74]. Other authors have investigated possible changes in retinal anatomy in patients with AD, reporting an abnormal reduction of retinal thickness (by OCT) [75] associated with defective blood flow [76].…”
Section: Alzheimer' Disease and Eye Pathologiesmentioning
confidence: 99%
“…The crystalline lens also could be involved in AD, and high levels of β-amyloid were described in lens epithelia of subjects with a particular and rare type of cataract, the anterior subcapsular cataract [73,74] in the number of optic nerve fibers, probably due to the toxicity on RGCs of β-amyloid, has been detected in some studies [78][79][80].…”
Section: Alzheimer' Disease and Eye Pathologiesmentioning
confidence: 99%
See 1 more Smart Citation